Therapeutic Efficacy of Wet Cupping on Uterine Inflammation in Primary Dysmenorrhea: An In Vivo Investigation Targeting Bilateral L4/L5 Vertebrae - Lestariningsih, Sri; Tamtomo, Didik Gunawan; Sulistyowati, Sri; Indarto, Dono; Soetrisno, Soetrisno; Muthmainah, Muthmainah; Pamungkasari, Eti Poncorini (Trends in Sciences, 2024)
Primary dysmenorrhea (PD) is a prevalent problem in gynecology affecting the quality of life for young women. This medical condition is often responsible for the absence of young women from school or work, increasing the risk of developing hyperemesis gravidarum in the future. Furthermore, PD causes pain due to the activation of the local PGF2α pathway in the endometrium, which triggers oxidative stress processes, uterine ischemia and spasmodic uterine contractions. The first-line therapies for PD, Nonsteroid anti-inflammatory drugs (NSAIDs) and oral contraceptives, can cause side effects such as headache, nausea, intestinal ulcers and platelet abnormalities. To overcome the impact of PD, cupping has been proven effective as an alternative pain therapy with minimal side effects. Therefore, this study aimed to evaluate the effects of cupping on writing latency threshold time, PGF2α levels and FP receptor expression in PD model rats. The experiment was conducted using female Sprague Dawley rats to analyze the effects of wet cupping therapy (WCT) on inflammatory repair in the uterus. The method used was a pre- and post-test control group design, with 35 female rats randomly divided into 5 groups. These consisted of normal control (NC), negative control (C−), positive control (C+) + ibuprofen 7.2 mg, as well as treatment groups, comprising dry cupping (DC) and WCT. The results showed that writhing time threshold of WCT was the same as C+ (p = 0.368), while PGF2α decreased in DC (43.43 pg/mL, p = 0.008) and WCT (189.25 pg/mL, p = 0.0154). Similar to C+, WCT significantly decreased serum PGF2α levels compared to C−. WCT also influenced the expression of PTGFR subunit similarly to NC, showing the capacity to control the inflammatory pathway. The study suggested that WCT was a promising therapeutic strategy for PD by decreasing PGF2α and PTGFR expression. HIGHLIGHTS Previous investigations conducted on experimental animals using wet cupping therapy (WCT) have shown histopathological results associated with primary dysmenorrhea (PD) caused by estradiol benzoate and oxytocin. Moreover, this study shows the potential of WCT in reducing inflammation-induced PD pain by inhibiting the expression of PGF2α and PTGFR in the cyclooxygenase pathway, potentially increasing the pain threshold. The results show that WCT offers a potential alternative therapy for PD caused by estradiol benzoate and oxytocin. GRAPHICAL ABSTRACT